Effects of recovery using contrast water therapy or compression stockings on subsequent 5-min cycling performance - Ménétrier, A.; Pinot, J.; Mourot, L.; Grappe, F.; Bouhaddi, M.; Regnard, J.; Tordi, N. (Journal of Science and Cycling, 2013)
Many researchers have investigated the effectiveness of contrast water therapy (CWT) or compression stockings (CS) during recovery, using subsequent performance as the principal outcome measure. However, data in the literature are contradictory, mainly because of the methodology used. Purpose: Based on well-controlled performance measures, this study aimed to compare the effects of CWT, CS or passive recovery (PR) on subsequent performance. Methods: After inclusion based on reproducibility criteria (intra-participant variability in performance test lower than the expected differences between the recovery interventions, i.e. 1.5%), 12 competitive male cyclists (peak power output: 5.0 ± 0.2 W/kg; cycling practice: 4.9 ± 0.4 times/week; intra-participant variability: 1.2 ± 0.2%) came to the laboratory three times in a random crossover design. Each time visit, they performed a tiring exercise on a cycle ergometer, followed by a 5-min performance test during which the mean power output was recorded, separated by a 15-min recovery period during which a 12-min PR, CWT (1:2 (cold: 10-12°C to warm: 36-38°C) min ratio) or CS (~20 mmHg) was implemented. Results: Compared with PR (353.8 ± 13.1 W), performance was significantly higher after CWT (368.1 ± 12.3 W) and CS (360.5 ± 14.8 W). Moreover, performance was significantly higher after CWT than after CS. Conclusion: Athletes can use this information as a way of improving their performance in competition format using repeated high-intensity exercises in a short period of time, such as in mountain bike, track or BMX races. Moreover, these data reinforce interest for researchers to consider performance tests with high test-retest reproducibility, especially when small but real benefits are expected.